Strategi Rektor Meningkatkan Mutu Sarana Prasarana di Institut Darul Sarolangun - Agil Munawar; Kemas Imron Rosadi; Kasful Anwar US (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study explores the strategies implemented by the Rector of Institut Darul Ulum Sarolangun to improve the quality of higher education infrastructure and facilities. The research focuses on how these strategies create a more conducive academic environment and support sustainable educational quality improvement. The strategies adopted include efficient financial management, where budget allocation is meticulously planned and measured for campus facility development and maintenance. The Rector actively fosters collaboration with various external stakeholders, including the Ministry of Religious Affairs, local government, private companies, and funding organizations such as BAZNAS. These partnerships offer additional funding opportunities and technical support essential for campus infrastructure development. Another crucial aspect is the focus on the well-being of the academic community. The Rector ensures that campus facility management not only focuses on physical infrastructure but also on enhancing services that support the welfare of students, faculty, and administrative staff. The study adopts transformational, participatory, and inclusive leadership theories as its analytical framework. These theories provide a robust foundation for understanding how visionary and collaborative leadership approaches drive innovation in the development of educational facilities. The findings reveal that the Rector's strategies, emphasizing participation and collaboration, positively impact the quality of campus facilities and foster a better academic environment. With this comprehensive approach, Institut Darul Ulum Sarolangun strengthens its competitive edge as a higher education institution oriented toward superior educational quality